A theoretical study of c-C5H8 adsorption on Ge (0 0 1)-2 × 1 and on dimer vacancies on the surface: Electronic structure and bonding - German, Estefania (2010)
In this work we analyzed the geometry and the chemical interactions for c-C5H8 adsorption on Ge (0 0 1), using density functional theory calculations (DFT). We examined the changes in the atomic interactions using a slab model. We considered two cases, the cyclopentene adsorption on Ge(0 0 1) and on dimer vacancies on the surface. We found an average distance H-Ge, -C-Ge and {double bond, long}C-Ge of 1.50, 1.70 and 1.65 Å, respectively, on dimer vacancies; and an average {double bond, long}C-Ge distance of 2.05 Å on Ge-Ge dimer. We also computed the density of states (DOS) and the DOS weighted overlap populations (OPDOS) corresponding to C-C, C-Ge, C-H, and Ge-Ge bonds. During adsorption the main contribution are the C{double bond, long}C double bond in both cases, and the next C and the H's belonging to this bonds in the case of adsorption on dimer vacancies. The orbital contribution includes participation of the 2py and 2pz orbitals corresponding to unsaturated C atoms, 2pz corresponding to side saturated C, and the 4p orbitals of Ge for the adsorption on dimer vacancies; 2s and 2pz orbitals corresponding to double bond C atoms, 4s and 4pz orbitals of Ge for the adsorption on Ge(0 0 1). © 2010 Elsevier B.V. All rights reserved.